Unidad y diversidad religiosa: reparos de la tolerancia en Pedro de Ribadeneira y Francisco Suárez - Amezúa, Luis-Carlos Amezúa (Cauriensia, 2023)
In Early Modern period, thinkers of the Second Scholasticism and the Society of Jesus contributed to facilitating greater closeness to cultural and religious diversity. In this article we compare the approaches of Pedro de Ribadeneira and those of Francisco Suárez. In them we find a response to the religious differences in modern Europe and within the Hispanic Monarchy of a relative openness, but this is more correct applied to the integrity of Suárez’s works than to those of other writers influenced by the reason of State, like Ribadeneira. Suárez’s reflections on the conversion of the moriscos were interpreted at the time as support for religious tolerance. And still today some academics value them as a model of respect for minorities useful for our time. However, these statements by Suárez are ambivalent and that is why I prefer to classify them as "tolerance objections", that is, because these ideas can facilitate freedom of worship, but they can also reinforce a tight control of particular ways of life. In any case, this Ignatian tradition offers an alternative potentiality of respect for alterity, more clearly in the work of Francisco Suárez than in that of Pedro de Ribadeneira.